Perebutan Otoritas Menikahkan Perempuan: Analisis Putusan Mahkamah Agung Nomor 02 K/AG/1985 - Muhammad Idris Nasution (Jurnal Studi Gender dan Anak, 2023)
Gender injustice against women has placed women in the implementation of marriage as objects, not as subjects. Guardianship in marriage which is basically intended for protection misses in reality. Guardianship actually sometimes hinders the realization of women's rights to marriage, thus getting resistance from some circles. This article will describe the phenomenon of the struggle for authority to marry women in the Supreme Court Decision Number 002 K/AG/1985, in which it is stated that parents and female guardians want to annul the marriage of a child because it was carried out with an illegitimate guardian. The courts of first instance and the level of appeal have annulled the marriage, but the Supreme Court at the cassation level considers the marriage to be legal according to Islamic law. The author in this article conducts a study with the type of normative legal research with a case study approach. Data sources come from primary, secondary, and tertiary legal materials. Data was collected by using document study and discussion methods. Then the data were analyzed qualitatively using content analysis techniques. The results of the author's analysis show that the Supreme Court wins women and gives them authority in their marriages. The implications of this consideration, the law of women marrying themselves, women representing their marriages and women becoming marriage guardians, will be discussed. The results of the study show that the Supreme Court's decision is gender-equitable, although it still needs to be criticized regarding the distinction between the status of girls and widows.